Angiografía coronaria normal. Una forma de evaluar el uso apropiado de la indicación de este estudio. - Ugalde P., Héctor; Morris C., Raimundo; Pino L., Ángela; Prat M., Hernán (Revista Hospital Clínico Universidad de Chile, 2023)
Coronary angiography remains the gold standard when studying coronary artery disease. Currently, there are guidelines on how to do this diagnostic procedure and the diseases that require its application, however, a significant proportion of inappropriate exams are reported, with increased risk to patients and overall healthcare costs. This has not been evaluated in our country. In this study the last 500 normal consecutive coronary artery angiographies on patients with suspected coronary artery disease and 50 with severe 3 vessel disease. Three cardiologist with different experience, blinded to the coronariography results, were asked to review the clinical data of the 550 patients and decide if they would perform or not a coronary angiography. Then data were analyzed to identify potential causes for normal coronary angiographies. The results showed that in 100% of severe three vessel disease patients, cardiologist would perform coronary angiography and in normal exams, 60% would be performed, with 40% of them would have been inappropriate, similar to literature. We can conclude that normal coronary angiographies with a good indication exist and a significant proportion of exams should not have been done, suggesting a more careful application of guidelines and improved non invasive testing before invasive exams.